2018
DOI: 10.1259/bjr.20170605
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of enhanced malignant and benign lesions on contrast-enhanced spectral mammography

Abstract: Despite variations in the degree of tumour angiogenesis, quantitative analysis of the breast lesions on CESM documented the malignancies had distinctive stronger enhancement and depressed relative enhancement patterns than benign lesions. Advances in knowledge: To our knowledge, this is the first study evaluating the feasibility of quantifying lesion enhancement on CESM. The quantities of enhancement were informative for assessing breast lesions in which the malignancies had stronger enhancement and more relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 25 publications
4
44
1
Order By: Relevance
“…[ 12 ] Deng et al reported that benign and malignant breast lesions have fundamentally different degrees of enhancement, and a high degree of enhancement suggests that lesions are likely malignant. [ 13 ] The results of the studies are consistent with our findings. However, neither of them combined BI–RADS with CESM enhancement to maximize the full benefits of CESM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[ 12 ] Deng et al reported that benign and malignant breast lesions have fundamentally different degrees of enhancement, and a high degree of enhancement suggests that lesions are likely malignant. [ 13 ] The results of the studies are consistent with our findings. However, neither of them combined BI–RADS with CESM enhancement to maximize the full benefits of CESM.…”
Section: Discussionsupporting
confidence: 92%
“…[ 12 ] Deng et al quantified the enhancement degree of CESM lesions and concluded that benign and malignant breast lesions have fundamentally different enhancement degrees, and a high CESM enhancement suggests that lesions are likely malignant. [ 13 ] These studies demonstrated that CESM enhancement can be used to differentiate benign from malignant breast lesions. However, they did not provide specific quantitative analysis criteria and thus their results cannot be directly applied to clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…For enhancement intensity, this preliminary research suggested that enhancement intensity of malignancies was usually stronger than that of benign lesions (Table 1), which was consistent with other researchers' findings 6,[11][12][13][14]17 . Lewin et al 6 concluded that 84.6% (11/13) of invasive cancers enhanced strongly, while all benign lesions (n = 12) were presented as no or weak enhancement qualitatively.…”
Section: Discussionsupporting
confidence: 90%
“…However, there is no research before investigating the correlation between enhancement intensity and hormonal receptor status of breast cancers. As for enhancement patterns, several published papers 4,13,15 claimed that the distribution of enhancement patterns between benign and malignant lesions was different, which was similar to time-intensity curve (TIC) on breast dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). Whereas, it is uncertain that how is the agreement between two modalities.…”
mentioning
confidence: 99%
See 1 more Smart Citation